2014
DOI: 10.1039/c4ra03613a
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of the polarization and dielectric properties of KNbO3 nanoparticles

Abstract: Ferroelectric nanostructures have recently attracted much attention due to the continuous demand of miniaturizing devices and discovering novel phenomena. Therefore, in depth study of the ferroelectric, and dielectric properties at various particle sizes in nanoscale ferroelectrics is of technological importance. Unfortunately, research aimed at discovering and understanding the size effect on the electric properties of ferroelectric nanostructures are scarce. Here, we investigate the spontaneous polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…It can be understood that the dielectric constant of smaller-sized nanoparticles exhibited a higher value, whereas, with an increase in particle size, the dielectric constant decreased. This is in agreement with previous findings [19]. In contrast, other studies reported that the dielectric constant increases with an increase in the size of nanoparticles [20].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It can be understood that the dielectric constant of smaller-sized nanoparticles exhibited a higher value, whereas, with an increase in particle size, the dielectric constant decreased. This is in agreement with previous findings [19]. In contrast, other studies reported that the dielectric constant increases with an increase in the size of nanoparticles [20].…”
Section: Resultssupporting
confidence: 93%
“…In order to theoretically estimate the contribution of the dielectric constant of pure ZnO nanoparticles to that of the composite, we used the modified Rother–Lichtenecker equation. The measured dielectric constant is given by the relation [19]: ε measured = exp [ln ε 1 + f 2 (1 − k ) ln ( ε 2 / ε 1 )] where ε measured , ε 1 , and ε 2 represent the dielectric constant of the ZnO/Ge composite, the polymer medium, and the ZnO nanoparticle, respectively, f 2 represents the volume fraction of the ZnO nanoparticle, and k is the shape dependent factor ( k = 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…Larger grain is in favor of piezoelectric properties enhancement because the motion of domain wall can be released more compared with small grain. [30][31][32] On the other hand, too much larger grains can deteriorate piezoelectric properties inversely, because of much more bubbles are generated during the process of grain excessively growing, and therefore the densication of the ceramics reduces. Transition temperature of ferroelectric-paraferroelectric phase (T C ) for x ¼ 0.02, 0.035, 0.045, 0.06 is also observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Birol et al [24] reported measuring a spontaneous polarization of 25 C cm −2 in polycrystalline KNbO 3 . Ge et al [25] studied the impact of crystal size on the polarization in KNbO 3 and found a spontaneous polarization of 40.3 C cm −2 . Kleemann et al [26] reported a spontaneous polarization of 37 C cm −2 .…”
Section: Resultsmentioning
confidence: 99%